Ögonbehandling av häst med lavage system och infusionspump Omvårdnadsaspekter : omvårdnadsaspekter - Kornbeck, Ellen (SLU/Dept. of Animal Environment and Health (until 231231), 2012)
Objective – To study the requirement of nursing care of the equine patient during eye treatment with a lavage system together with a constant rate infusion pump.